Effect of Active Smoking During Pregnancy on Women and Newborn Health - Yanikkerem, Emre; Ay, Semra; Çalim, Selda lldan (International Journal of Child Health and Nutrition, 2014)
The aim of the study was to identify the effect of prenatal smoking on mother and newborn health. The study was carried out in 700 women, who delivered at Merkez Efendi Maternity and Children’s Hospital between 1st January, 2011 and 31st December, 2011. Of the sample of women, 15.6% were current and 7.3% were quitting smokers. Women who continued smoking during pregnancy lived in households with husband who smoked and had higher rates of depressive symptoms and pregnancy included hypertension. Smoker women more likely reported to expose physical violence during pregnancy by their partner. Meconium in amniotic fluid was associated with women smoking status. Newborns who were exposed to tobacco smoke prenatally had deficits in weight (-186.6 gr), height (-0.9 cm) and head circumference at birth (-0.6 cm). In the study when women quit smoking during the first trimester, their infants have anthropometric measures similar to infants of nonsmokers. Smoking during pregnancy was related to low birth weight, height, and with small head circumference. Smoking cessation during pregnancy may have a greater impact on baby anthropometrics measures which were similar to infants of nonsmokers. To protect the health of their future unborn children, it would be optimal to target all women of reproductive age to quit smoking before they consider becoming pregnant.